Investigation of application and development of precision irrigation technology - Szabó, Andrea; Tömöri, F; Vad, Attila Miklós; Tamás, János; Nagy, Attila (International Journal of Engineering and Management Sciences, 2019)
Due to the extreme weather conditions irrigation is nowadays considered an increasingly necessary factor. After evaluating the water requirements of the plant and the available water resources is necessary to decide what irrigation method to use. One of the most commonly used methods in field conditions is rain-type irrigation, of which there are several types (eg linear, winding drum). The uniformity of the field nozzles can be characterized by the Christiansen uniformity factor (CU%) and the distribution uniformity factor (DU%). The coefficients can be derived from the volume of water captured by the rain gauges. Our investigations were carried out in July and August 2019 at the University of Debrecen's Vision Plant Experimental Plant and at a linear irrigation equipment of a Nyírbátor company. The aim of the study was to compare the uniformity of water dispersion applied by conventional linear technology and precision linear irrigation technology. In addition we examined the intercept values of maize.